சிலப்பதிகாரத்தின் வணிகப் பரிமாணம்: The Commercial Dimension of Silappatikaram - சதிஷ் ர (KALANJIYAM - International Journal of Tamil Studies, 2026)
This article examines the unprecedented occurrence of selecting characters with a commercial background as the protagonists in Silappatikaram, the first epic composed in the Tamil literary tradition. The paper highlights how the Jain religion, while using the epic Silappatikaram to give literary form to its philosophy, simultaneously elevates the mercantile community—which heavily supported it socially and held immense influence in contemporary society—to the prestigious position of leading the epic narrative. The commercial dimension of Silappatikaram is uncovered by analyzing the intersections that trade maintained with governance, religion, and philosophy within the epic. This study reveals how religion, philosophy, and commerce functioned in harmonious tandem within the text to ensure their respective long-term stability. Furthermore, through the references to trade in Silappatikaram, this research demonstrates how the commercial sphere effectively created Silappatikaram as its own literary representation.